Constant and Variable Railroad Expenditures and the Distance Tariff - Lorenz, M. O. (Quarterly Journal of Economics, 1907)
Journal Article Constant and Variable Railroad Expenditures and the Distance Tariff Get access M. O. Lorenz M. O. Lorenz University of Wisconsin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 21, Issue 2, February 1907, Pages 283–298, https://doi.org/10.2307/1883434 Published: 01 February 1907